Implementasi Kebijakan Sistem Penanggulangan Gawat Darurat Terpadu Di Kota Bitung (Studi Tentang Public Safety Center) (Pengelolaan Sumberdaya Pembangunan, 2021)
Integrated Emergency Management System which has the aim of improving the handling of emergency cases, namely the handling of pre-accident cases. In this study, researchers wanted to know how the implementation of this SPGD was carried out through the Public Safety Center (PSC) in the city of Bitung. This research is a descriptive research with a qualitative approach. Using data analysis techniques from Miles and Huberman consisting of data reduction, data presentation and verification. Based on the results of the study, it was found that the implementation of the Public Safety Center (PSC) 119 of Bitung City had not been very effective. Namely, the lack of infrastructure and infrastructure that is owned and does not meet standards, the sources of funding that are owned are not flexible, do not have a network of partnerships with other agencies, nurses need to increase their special expertise in handling emergency cases, and for implementers a more informative attitude is needed in delivering the program. as well as the form of services provided by the Public Safety Center (PSC) 119 for the people of the city of Bitung.Keywords: Policy, Public Safety Center